Est-ce reel? : phenomenologies de l'imaginaire - Dufourcq, Annabelle. (Studies in Contemporary Phenomenology, 2016)
While realism has enjoyed renewed vigor in contemporary philosophy, Est-ce réel ? Phénoménologies de l'imaginaire challenges the relevance of the concept of reality from a phenomenological perspective. The volume brings together an exciting and provocative range of contemporary research on these issues, moving beyond the classical opposition between the real and the imaginary. Est-ce réel? gathers original contributions from a selected group of specialists, including internationally acclaimed scholars as well as emerging researchers. The collection demonstrates a vast new territory unfolding in contemporary philosophy, from ontological reflections on the imaginary to the analysis of the fundamental aesthetic, ethical, socio-political, and therapeutic implications that follow from them. With texts by G. Chernavin, A. Coignard, A. Dufourcq, I. Fazakas, A. Gléonec, A. Hervy, U. Idziak-Smoczyńska, A. Koubova, C. Lapierre, Y. Murakami, F. Pignarre, D. Popa, E. de Saint Aubert, J. Sallis, A. Schnell, R. Steinmetz et J.J. Wunenburger.